A reconfiguração da notícia : um estudo sobre o impacto do ciberacontecimento na rotina produtiva no telejornalismo - Santos, Leandro Olegário dos (2018)
The general objective of this doctorate thesis is to analyze the newsworthiness criteria used in the news reports featured on the television program Almoço, from RBS TV Porto Alegre newsmaking on brazilian television. The chosen object of this study, featured on the leading broadcaster in Rio Grande do Sul, is the oldest on the local programming grid and has been on air for 46 years. In the context of convergence and digitization of journalistic processes, we try to answer as to how events promoted on social network conquer a news dimension on television. The Content Analysis of Laurence Bardin (2011) was used, with inspirations and approximations to the ethnomethodology of Alain Coulon (1995). In-depth i observation of the productive routine in the production and editing stages of the electronic magazine, between August and September 2017, to analyze the five news reports exhibited in the same data interpretation: news report analysis and interview analysis. The first having as registration units Criteria of Newsworthiness, Content Presence, News Reporting Time and Event Platform, and the second, Prac Accountability and Member Notion. In the broadcasters’ search for a new connection with the audience, the results show that the hypertelevision paradigm causes newsworthiness criteria to change, modifying the jou a different news value. Reflecting upon the subject, we propose the identification of cyberevent phases to the journalistic agenda, experienced by television journalists.